(untitled) (Scientific journal of the Fergana State University, 2024)
This article is about the possibilities of contamination in increasing the level of expressiveness in artistic and tourist-advertising discourses. This issue has become a topical subject of today’s research, because the period of modern development of any language is characterized by the emergence of new discourses as special units of the language. Therefore, the discourse and the special language units cannot be separated from each other. By the way, they are characterized by crossing each other and enriching each other to a certain extent. Despite the fact that, discourse is a relatively new field in linguistics, it has already been studied by foreign linguists. The expansion of the scope of research leads to its deeper conquest. Discourse and its types, including media discourse, political discourse, gluttonous discourse, artistic discourse, and touristic discourse, are the products of these researches. Within this topic, the works of foreign linguists such as M. Foucault, Z. Harris, E. Benviniste, U. Chase, V. Deisler, J. Grimes, Teun Van Dyck, A. E. Kibrik, V. Karasik, V. Demyankov, N. Arutyunova, V. I. Karasik, E. Chernyavskaya are incomparable. For example, V. V. Zirka, T. V. Matveeva worked on linguo-pragmatic problems of discourse; N. V. Kulibina, T. B. Samarskaya, E. Martirosyan on the problems of artistic discourse; and on the problems of touristic discourse the works of L. P. Tarnayeva, V. V. Datsyuk, N.V. Filatova are really worthy. However, the problem of the interaction of artistic and tourist discourse in the advertising genre has not yet become an object of special research. From this point of view, the purpose of this article is to analyze the possibilities of contamination in the artistic discourse established in the tourist advertising discourse.